INCREASING PATIENT AND FAMILY AWARENESS OF THE EARLY SIGNS OF A HEART ATTACK AT AL-IHSAN HOSPITAL, BANDUNG - Aminah, Siti; Hendi, Oman; Barus, Sada Ukur; Tampubolon, Briefman; Hardian, Ratna Wulan; Nidaulhaq, Pandu (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Heart attacks are a leading cause of death in Indonesia and globally, yet public awareness of the early warning signs remains low. Educating patients and their families is crucial to improving preparedness for this condition. This community service activity was conducted at Al-Ihsan Regional Hospital in Bandung using an educational-participatory approach. The implementation method included interactive lectures, group discussions, role-playing simulations, and pre- and post-tests. Fifty participants, including patients with a history of heart disease and their families, participated. Pre-test results showed that 73.3% of participants had low to moderate knowledge levels. After the educational intervention, knowledge scores increased by 35%, with 88.9% of participants answering more than 80% of the post-test questions correctly. Participants also demonstrated a better understanding of recognizing symptoms and taking appropriate emergency measures. The interactive educational program has proven effective in increasing patient and family awareness and preparedness for the early warning signs of heart attacks. This approach can serve as a model for applicable preventive interventions at the community level. Keywords: Heart attack, interactive education, family awareness, early signs, community service